Influence of structural parameters on characteristics of flow field in vessel-shaped aquaculture cages - Hongzhou Chen; Xucheng Jiang; Dejun Feng; Xu Yang; Lili Mei (Ocean Engineering, 2026)

Biomass models, allometric relationships, and carbon sink of Sargassum henslowianum in Nan'ao Island - Jing Chen; Jinhuai Ni; Hong Du; Kai Zong; Sunzhaocong Lan; Jianpeng Lu; Dejun Feng; Xu Yang; Guangyang Zhang; Lili Mei; Yuanmin Sun; Xunmeng Li (Regional Studies in Marine Science, 2026)

Laboratory Investigation of the Uplift Resistance of a New Winged H-Pile Anchor Developed for Offshore Marine Aquaculture - Xu Yang; Lianghao Tang; Lili Mei; Tianyuan Zhang; Shuai Niu; Zhefei Sun; Zhenliang Wang; Dejun Feng; Fukun Gui (Journal of Marine Science and Engineering, 2025)
To enhance the stability and safety of marine aquaculture facilities by addressing the limited uplift resistance capacity and susceptibility to deflection of conventional straight-shafted piles, this study introduces an improved H-pile anchor and conducted laboratory experiments. The new anchor incorporates resized H-piles with wing plates added to both sides, optimized for area and placement, as well as an adjusted loading angle. The findings demonstrate a positive correlation between the uplift resistance capacity of the H-pile anchor and its length and width, indicating that while increased pile length significantly enhances resistance, widening has a minimal impact. Additionally, enlarging the wing plate area improves the resistance; however, efficiency (δ) decreases with the increase in the area, suggesting the existence of an optimal size. The optimal wing plate dimensions (L = 80 mm, W = 25 mm) improve uplift resistance by at least 10.6% compared to non-wing pile anchors. Furthermore, positioning the wing plates at the base of the pile anchor rather than the top enhances resistance by approximately 13.8%. Setting the anchor layout angle to 45° reduced the displacement under inclined loads. This research provides essential theoretical support and practical guidance for strengthening the safety and stability of marine aquaculture facilities.

Composites ZSM-5/KIT-6 Synthesized Via Assembly Modification Procedure and Mechanical Grinding Procedure, Respectively, and Their Application to CO2 Adsorption - Zhifeng Lin; Jianwen Wei; Linlin Geng; Dejun Mei; Lei Liao (Water, Air, & Soil Pollution, 2017)

Spatial uniformity in the mineralogical and geochemical compositions of surface sediments in Lake Qinghai and their controlling factors - Liu-Mei Chen; Zhangdong Jin; Dejun Wan; Fei Zhang (Limnology, 2015)